STUDI NASKAH TASAWUF ABDUL MALIK BIN ABU BAKAR KRUI PENENGAHAN LAHAI - Hermansyah, Hermansyah; Mahrus, Erwin; Sulaiman, Rusdi (JURNAL PENELITIAN KEISLAMAN, 2010)
Some experts argue that Islam initially spreading in the archipelago was highly influenced by Sufism. One of the advantages of the approach taken by Sufis was that Islam was relatively tolerant with local culture. Because of such an approach, various local people could easily accept Islam, including those coming from rural and remote areas. Some Muslim religious scholars (ulama) recorded this Islamization in their works and manuscripts. One of the manuscripts was written by Abdul Malik bin Haji Abu Bakar Krui Penengahan Lahai. This important document was found in an inland area of West Kalimantan. Through philological and historical examinations to this manuscript, this study finds that Sufism that was spreading in that area was affiliated to Qadiriyah wa Naqsyabandiyah sufi order. The text explicitly refers to Fath al-âÃrifin work, written by Khatib Sambas, the founder of the Qadiriyah wa Naqsyabandiyah sufi order. One important teaching offered by this Sufism is the integration between sharia and tasawuf. The text also reveals that the spread of Islam did not neglect to accommodate local culture.